2021
DOI: 10.1101/2021.12.06.471373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cathelicidin-3 associated with serum extracellular vesicles enables early diagnosis of a transmissible cancer

Abstract: The identification of practical early diagnosis biomarkers is a cornerstone of improved prevention and treatment of cancers. Such a case is devil facial tumour disease (DFTD), a highly lethal transmissible cancer afflicting virtually an entire species, the Tasmanian devil (Sarcophilus harrisii). Despite a latent period that can exceed one year, to date DFTD diagnosis requires visual identification of tumour lesions. To enable earlier diagnosis, which is essential for the implementation of effective conservatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…Since the emergence of a coordinated response to the DFT1 epidemic, developing a test for the early detection of DFTD has been a high priority for conservation management [50]. Using contemporary methodology for the isolation of EVs and quantitative proteomics, we demonstrated the means to develop an early DFT1 diagnostic [51]. Our study found that the protein cathelicidin-3 (CATH3) was enriched in serum EVs of both devils with clinical DFT1 infection and latent devils 3-6 months before diagnosis.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Since the emergence of a coordinated response to the DFT1 epidemic, developing a test for the early detection of DFTD has been a high priority for conservation management [50]. Using contemporary methodology for the isolation of EVs and quantitative proteomics, we demonstrated the means to develop an early DFT1 diagnostic [51]. Our study found that the protein cathelicidin-3 (CATH3) was enriched in serum EVs of both devils with clinical DFT1 infection and latent devils 3-6 months before diagnosis.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%